AB1355-HPR A SYSTEMATIC LITERATURE REVIEW (SLR) ON NURSING SENSITIVE OUTCOMES IN SYSTEMIC SCLEROSIS (SSC). (June 2019) - Aoufy, Khadija El; Rasero, Laura; Piemonte, Guya; Virgili, Gianni; Guiducci, Serena; Bruni, Cosimo; Randone, Silvia Bellando; Matucci-Cerinic, Marco
Abstract : Background: SSc affects significantly patients functionality and Quality of Life (QoL). Specific Nursing Sensitive Outcomes (NSOs ) still need to be established in SSc. Objectives: This SLR was aimed at identifying NSOs in SSc patients and the related screening tools. Methods: Medline, CINHAL, EMBASE and PsycINFO were searched to identify relevant studies. Experimental and observational studies that reported nursing interventions and NSOs were included. All potentially eligible studies were read in full text and examined against the selection criteria previously listed. Quality assessment was carried out through Critical Appraisal Skills Programme tools; and, the OMERACT ( Outcome Measures in Rheumatology ) comprehensive conceptual framework for health was used to contextualise and summarize findings. Results: 7015 records were screened for title and abstract, 39 full-text were identified and assessed. Eleven studies were included in this SLR. For the core area " pathophysiological manifestations " 4 domains (healths status, digital ulcers, clinical efficacy and fatigue), and, for the core area- " impact on life "- 5 domains were found (functionality, patient knowledge, patient satisfaction, psychological status and quality of life). Thus, NSOs identified were physical function and parameters, health events, upper limb functionality, patients knowledge of disease complications, degree of self-management, need for nursing instructions, self-efficacy, health efficacy, psychological state, depressive mood and QoL. Conclusion: T he results identify outcomes that may allow the structuring of a preliminary behavioural flow chart for nursing SSc case management. Further researches are warranted to examine the multidimensional and complex role of nursing in SSc management. Flow chart of the SLR: Disclosure of Interests: Khadija El Aoufy: None declared, Laura Rasero: None declared, Guya Piemonte: None declared, Gianni Virgili: None declared, Serena Guiducci: None declared, Cosimo Bruni: None declared, Silvia Bellando Randone: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: Actelion, BMS; MSD, Janssen